2015
DOI: 10.1039/c4ee02977a
|View full text |Cite|
|
Sign up to set email alerts
|

Comment on “Environmentally responsible fabrication of efficient perovskite solar cells from recycled car batteries” by Po-Yen Chen, Jifa Qi, Matthew T. Klug, Xiangnan Dang, Paula T. Hammond and Angela M. Belcher, Energy Environ. Sci., 2014

Abstract: A paper published in Energy and Environmental Science by Po-Yen Chen et al. reported on a new route for fabricating perovskite solar cells using ''recycled car batteries'' (spent lead acid batteries) as starting materials. Multiple lines of evidence show that it was a new lead acid battery and not a recycled one that was used to synthesize lead iodide perovskite materials in this work. As the components of electrodes are different between new batteries and spent ones, this fabricating method would not be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Furthermore, Chen et al demonstrated the successful fabrication of perovskite solar cells using the lead from recycled batteries, obtaining PCE=9.37%, almost the same as PCE obtained using a commercial supplier of PbI 2 ; with the lead recovered from a single lead-acid car battery ∼700 m 2 of PSCs can be fabricated [168]. This result was commented on by Li et al who pointed out that the experiments were carried out with a new battery and that a spent electrode will pose major difficulties toward the effective realization of this interesting recycling route [169], a comment that was replied to by Chen et al [170]. This discussion about the possibility of Pb recycling and its application to PSC fabrication deserves a future detailed Life Cycle Assessment based on the existing and eventually additional experimental evidence.…”
Section: Recyclingsupporting
confidence: 61%
“…Furthermore, Chen et al demonstrated the successful fabrication of perovskite solar cells using the lead from recycled batteries, obtaining PCE=9.37%, almost the same as PCE obtained using a commercial supplier of PbI 2 ; with the lead recovered from a single lead-acid car battery ∼700 m 2 of PSCs can be fabricated [168]. This result was commented on by Li et al who pointed out that the experiments were carried out with a new battery and that a spent electrode will pose major difficulties toward the effective realization of this interesting recycling route [169], a comment that was replied to by Chen et al [170]. This discussion about the possibility of Pb recycling and its application to PSC fabrication deserves a future detailed Life Cycle Assessment based on the existing and eventually additional experimental evidence.…”
Section: Recyclingsupporting
confidence: 61%
“…Lead‐PSCs can be thought of as lead‐storage devices, avoiding lead disposal and/or extraction when other lead containing devices reach their end‐of‐life. A recent research study has pointed out that these devices can be viewed as a long‐term storage for lead that has been recycled from car batteries . This “storage” will depend on the lifetime of the devices.…”
Section: Specifications For the Perovskite Solar Cells Considered In mentioning
confidence: 99%
“…OHPs bear the risk of leakage into the environment by rain water due to the high solubility, but the positive aspect is that Pb 2+ can also be recovered by simple solution treatment due to this feature. Besides the recovering of Pb from PSCs, waste Pb from batteries can be reused to produce PbI 2 for the fabrication of PSCs . Apart from environmental concerns, the manufacturing cost and energy consumption in manufacturing PSCs have to be considered.…”
Section: Environmental Impactmentioning
confidence: 99%